2014
DOI: 10.5296/ijafr.v4i2.6462
|View full text |Cite
|
Sign up to set email alerts
|

Impact of International Financial Reporting Standards on Cost of equity Capital for Asian countries

Abstract: The present study examines whether adoption of IFRS reduces Cost of equity Capital for firms in Asia. The sample consists of firms from four Asian Countries, namely China, Hong Kong, Israel and Philippines, where IFRS has been made mandatory. Data for six years covering the period from 2006-2011 has been taken for analysis. Different types of panel data estimates were used and compared so as to interpret the results with the best suited parameters for different data sets for different countries. The results va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
8
1
1
Order By: Relevance
“…The above potential benefits along with greater "willingness and capability" of reporting are expected to motivate firms to disclose their ICR better, most of which is in the form of narrative in firm documents. Contrary to the above, Patro and Gupta (2014) found only two countries (out of four studied) with lower cost of equity post-IFRS.…”
Section: Objectives and Motivationcontrasting
confidence: 85%
“…The above potential benefits along with greater "willingness and capability" of reporting are expected to motivate firms to disclose their ICR better, most of which is in the form of narrative in firm documents. Contrary to the above, Patro and Gupta (2014) found only two countries (out of four studied) with lower cost of equity post-IFRS.…”
Section: Objectives and Motivationcontrasting
confidence: 85%
“…Ng and Zabihollah (2015) considered the link between the cost of capital and the overall sustainability of business undertakings, with due consideration of environmental and social factors, and concluded that the correlation between sustainable growth and cost of equity capital tends to strengthen with the increase in performance. Padro and Gupta (2014), having conducted their studies in the Asian countries, point to the significance of adopting international accounting standards for determining the cost of capital. Prior research of Easley and O'Hara (2004) argues that not only the scope of information presented but also the structure of information was relevant for determining the cost of capital (this was certainly related to the measurement of the value of assets).…”
Section: Understanding the Cost Of Capitalmentioning
confidence: 99%
“…Accounting quality also increases as there is a lower chance of earning management in the financial statements (Bartov, Goldberg, & Kim, 2005), more foreign mutual funds investments are attracted (Covrig, Defond, & Hung, 2007), efficiency increases in the form of debt contracting (Kim & Shi, 2012), and forecasting errors are reduced by the financial analysis (Ashbaugh & Pincus, 2001). The cost of equity capital decreased for Asian countries after adopting IFRS (Patro & Gupta, 2014). The present paper contributes to this stream of literature by focussing on the impact of IFRS adoption on stock price synchronicity 1 in China, Hong Kong, Israel, and the Philippines (hereafter, "the selected Asian markets").…”
Section: Introductionmentioning
confidence: 99%